Analisis dan Perancangan Sistem Pembelian, Persediaan dan Penjualan pada CV Mulia Baru - Alda, Muhamad; Sherliyanda, Dwika; Ninta, Meilisa; Fatyana, Nadya (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
CV. Mulia Baru is a shop engaged in the sale and purchase of household appliances. CV. Mulia Baru is always crowded with customers both from within the city and from outside the city. The goods sold also vary, such as cabinets, tables, stoves, dispensers and so on. The buying and selling process can be done in cash and credit payments, for cash payments there are no significant obstacles, but credit payments often occur in paying debts to suppliers and collecting receivables from customers being late. Inventory information is also not update. The purpose of this system design is to produce a blueprint of an information system that fits the needs and business processes of the CV. New Highness. The methodology used for system design is the System Development Life Cycle (SDLC) methodology. The design of the system input design uses Visual Studio 2017 and the output uses Crystal report. The results of this writing are expected to be used by CV. Mulia Baru as a reference in realizing an information system that helps improve its operational performance